COMUNIDADES VULNERABLES Y DERECHOS HUMANOS - Camacho Monge, Daniel (Universidad de Costa Rica, 2023)
The category "human rights" is not immobile or definitive or it is the same in all circumstances of space and time. More than a general category, it is a dynamic of struggle for the dignity of individuals and groups depending on the time and place. In this process of struggle, the category of vulnerable communities has emerged to refer to sectors that, due to their cultural, economic and social subordination, are exposed to ignorance and disrespect for their rights and dignity.